Tantangan Mahasiswa Dalam Melafalkan Mantra Sanskerta - Ida Kade Suparta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Students often face challenges in reciting Sanskrit mantras, such as incorrect pronunciation, difficulty adapting to and following proper mantra articulation, and a lack of confidence when leading prayers using Sanskrit mantras. These issues can limit their ability to fully comprehend the essence and spiritual values embedded in Hindu religious practices. This study aims to explore the main factors contributing to students’ difficulties in reciting Sanskrit mantras. A qualitative method was employed, utilizing data collection techniques such as participant observation, unstructured interviews, and documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that students’ challenges in correctly pronouncing Sanskrit mantras involve phonetic and graphemic aspects, a lack of understanding of mantra meanings, memory-related issues and difficulty in changing habits, as well as psychological factors that weaken learning motivation. These findings highlight the need for a holistic learning approach that encompasses understanding meanings, fostering correct pronunciation through collective practice, and strengthening phonetic awareness both in the learning environment and in daily life.